Youth Culture and Globalization: The Articulation of Tradition, Modernity, and Postmodernity in the Youth Culture of Students of the University of the Philippines, Diliman - Lanuza, Gerardo M. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 1 No 1 (2000), 2007)
Introduction In my study of youth culture among the students of the University of the Philippines, Diliman, I was surprised to find out that despite the steady phase of modernization in the larger Philippine society, the youth culture of the students still betrays dominant traditional values and traits. I was surprised, that, given the fact that the university is a spatial field where modernization has its very likely stronghold, the students are very much attached to family values and traditional values associated with it. This paper is an attempt to explain this phenomenon, while at the same time connecting my analysis to the wider issue of globalization. My analysis is very tentative and is based mainly on my study of youth culture of the University of the Philippines. The analysis therefore can only be considered as preliminary and may not necessarily be applied to other forms of youth culture and subculture in other localities without further qualifications.